Perancangan Animasi 3D Bertemakan Islami dengan Judul “Adab Makan dan Minum” Menggunakan Metode Pose to Pose - Widia Saraswati (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
3-dimensional animation can be regarded as a moving image that is in a 3-dimensional digital space. In making this animation, it is done by imitating something real into the form of an animated image, using a virtual camera to make this 3-dimensional animated film and later will produce a video from the rendering process. In working on this 3-dimensional animation, all processes are done through computer assistance. The manufacturing process is through the Blender software version 2.8, which is an open source 3-dimensional computer graphics software that can be downloaded for free on the official website. The method used in this 3-dimensional animation is the "Pose-to-Pose" method, namely by making key movements or keyposes so that the existing movements appear smoother. This 3-dimensional animated film is designed with the aim of educating and informing about the procedures for a Muslim to eat and drink. As for this 3-dimensional animated film, it informs that the importance of eating and drinking etiquette is expected. The design of the 3-dimensional animated film that is made is expected to produce an animated film that can educate the audience so that they can reap the moral messages that have been presented.